The CD36 protein functions as an immunogenic domain of the RT8 alloantigen - Mlejnek, P; Kren, V; Liska, F; Zídek, V; Landa, V; Kurtz, T W; Pravenec, M (European journal of immunogenetics, 2003)
Completely concordant distributions of Cd36 and Rt8 deletion/null and wild-type alleles among inbred and congenic strains, together with Western blot analysis of RT8/CD36 proteins, indicated that the CD36 protein functions as an immunogenic domain of the RT8 alloantigen.
Keywords: isoantigeny; antigeny CD36; krysa rodu Rattus; Animals; potkani inbrední SHR; western blotting; lidé; zvířata; přenašeče organických aniontů; Organic Anion Transporters; Blotting, Western; Rats; Rats, Inbred SHR; CD36 Antigens; Isoantigens; Humans